ANALYZING THE REPRESENTATION OF MENTAL HEALTH IN HEALING FICTION: A CASE STUDY OF BOOK'S KITCHEN NOVEL - Suryanti, Dewi (JETA (Journal of English Teaching and Applied Linguistic), 2024)
This article explores the narrative of mental health within the realm of healing fiction, using Kim Jee Hye's novel Book’s Kitchen as the primary focus of analysis. By concentrating on the characteristics of the 'healing fiction' genre, we connect the novel's narrative to the broader field of medical narratives and consider the potential benefits of this relationship. Through an in-depth analysis of the novel using narrative analysis method, we conclude that healing fiction, Book’s Kitchen offers a form of therapeutic aid to its readers. It offers a self-reflection, and transformative tool to understand oneself mental health.